Effects of a social participation-focused virtual reality intervention for community-dwelling stroke survivors with physical disabilities: a randomised controlled trial protocol. Issue 7 (5th July 2022) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Lau, Alexander Yuk Lun; Lee, Vivian Wing Yan; Choi, Kai Chow; Kwok, Eddie Chi Fai; Thompson, David R
Abstract : Introduction: Studies show that stroke survivors encounter physical and psychological limitations that restrict their participation in social and community activities. Systematic reviews have yielded inconclusive evidence regarding the effectiveness of different interventions intended to support stroke survivors' social participation. Recent advances in virtual reality technology may offer promising solutions, although the optimal approach to enhance social participation among stroke survivors is yet to be determined. This trial aims to develop and evaluate the effectiveness of a social participation-focused virtual reality (SP-VR) intervention on the physical, psychological and social outcomes of community-dwelling stroke survivors with physical disabilities. Methods and analysis: A two-arm randomised, controlled, assessor-blind clinical trial will be conducted with 250 stroke survivor–caregiver dyads recruited from three acute and one rehabilitation hospitals, and three stroke nurse-led clinics. Participants will be survivors of a first or recurrent stroke within 6 months of stroke onset and able to remain in a sitting position without support, and their primary caregivers. Eligible participants will be randomly allocated to receive the SP-VR intervention or usual care which includes conventional physical therapy services. The intervention group will receive a newly developed 6-week novel custom-made SP-VR application comprising two sessions weekly. Three SP-VR modules will cover key aspects of survivors' social health needs, namely functional rehabilitation, social participation, and social interaction and recreation. The primary outcome for stroke survivors is social participation, and secondary outcomes include depressive symptoms, participation self-efficacy, physical function, functional mobility and social support. User satisfaction will be evaluated among both survivors and caregivers. Data will be collected in person at baseline, immediately after, and 3 months postintervention. Ethics and dissemination: Ethical approval has been obtained from the Joint Chinese University of Hong Kong-New Territories East Cluster Research Ethics Committee (Ref. No.: 2019.676). Study results will be disseminated through peer-reviewed journals and conference presentations. Trial registration number: ChiCTR2100050850.